Race and ethnicity an anthropological focus on the United States and the world (Princeton, N.J. Recording for the Blind & Dyslexic, 2002)
This book is an introductory survey of the basic concepts and research in the field of anthropology on race and ethnicity in the United States and throughout the world ... This text is a collection of ... essays for undergraduate students.-Pref.
Anthropology of race and ethnicity: Anthropology of race and ethnicity / R. Scupin; Concept of race in anthropology / S. MacEachern; History of "scientific" racialism / L. Lieberman; Ethnicity / R. Scupin; Ethnicity and ethnocentrism, are they natural ? / D.E. Brown -- Anthropology of race and ethnicity in the United States: U.S. ethnic relations, Anglos and the "white ethnics" / R. Scupin; American Indians / R.A. Bonney; African Americans / S. Love Brown ; Jewish Americans / J. Glazier; Hispanic Americans, Latinos / E. Bigler; Asian Americans / J. Benson; Arab Americans / B.C. Aswad -- Race and ethnicity, a global focus: Latin America and the Caribbean / R. Kephart; Africa / S. Clarke-Ekong; Middle East / L. King-Irani; Asia / R. Scupin; Pacific Islands / K. Brison; Europe / P. Ballinger; Canada / N. Buchignani; Conclusion / R. Scupin.
Originally published: Upper Saddle River, N.J. : Prentice Hall, c2003.
Includes bibliographical references.
Keywords: Anthropology -- Philosophy; Ethnic relations; Ethnicity; Ethnicity -- United States; Race relations; United States -- Ethnic relations; United States -- Race relations